Application of Lactobacillus casei 01 and oligofructose-enriched inulin in ayran - Tanja Petreska Ivanovska (Macedonian Journal of Chemistry and Chemical Engineering, 2018)
This study aimed to develop a probiotic/synbiotic ayran with a sufficient number of live bacteria Lactobacillus casei 01 (L. casei 01) during the product shelf-life. Under conditions of refrigerated storage for 15 days, probiotic survival and organic acid (lactic, acetic, propionic and butyric acid) production were evaluated. Simultaneously, pH, titratable acidity, total solids, and carbohydrate, protein, fat and mineral contents of the samples were examined. Overall results of the chemical analyses indicated the quality of the prepared samples to be comparable with the conventional ayran used as a matrix for probiotic/synbiotic supplementation. L. casei 01 survived better in ayran containing synbiotic chitosan–Ca–alginate microparticles compared to samples enriched with non-encapsulated probiotic alone or with synbiotic (L. casei 01 + oligofructose-enriched inulin), followed by increased production of lactic, acetic and propionic acid. Probiotic/synbiotic ayran may contribute to a healthy diet for consumers, while the sample enriched with microencapsulated formulation is advantageous in terms of probiotic activity.